Optimized Extraction, Microencapsulation, and Stability of Anthocyanins from Ardisia compressa K. Fruit - Maria Vianey Antonio-Gomez; Yolanda Salinas-Moreno; Francisco Hernández-Rosas; Fernando Martínez-Bustos; Isaac Andrade-González; José Andrés Herrera-Corredor (Polish Journal of Food and Nutrition Sciences)
The fruit of Ardisia compresssa K. is called chagalapoli and has a high anthocyanin content, with a profile dominated by malvidin derivatives. The aims of this study were: a) to determine optimal conditions (ethanol concentration, pH, and sonication time) for anthocyanin extraction from chagalapoli fruit (CF) using response surface methodology, b) to perform spray-drying microencapsulation of the anthocyanins using mixtures of polysaccharides (maltodextrin – M and Capsul® – C) as wall materials, and c) to evaluate the stability of microcapsules during storage. Of the variables examined to optimize anthocyanin extraction from CF, only ethanol concentration and pH were significant in the model. The optimal extraction conditions were: 63.5% ( v/v ) ethanol, pH of 2.0, and sonication time of 30 min, which led to an anthocyanin content of 1545 mg malvidin 3- O -galactoside equivalents/100 g of fresh fruit. The proportion of M/C as the wall materials for microcapsule (MC) preparation did not affect the encapsulation efficiency and anthocyanin retention, but high hygroscopicity was observed in the MC with a high proportion of M. The half-life of the MC ranged from 423 to 519 days, and no effect of wall materials was observed. The color stability of the MC was enhanced by increasing C proportion in wall materials. The high stability of microencapsulated anthocyanins of chagalapoli fruit makes it a suitable option as a food colorant.